Myokardszintigraphie mit kationischen 99mTc-Komplexen - Dudczak, R.; Angelberger, P. (Nuklearmedizin - NuclearMedicine, 1987)
This report summarizes the results which have been achieved by the use of 99mTc-labeled cationic complexes for myocardial scintigraphy. Radiopharma-cological aspects of 99mTc(lll)-CI2 (D.MPE)2 and 99mTc(l)-TBI as well as their scintigraphic behaviour in patients with coronary artery disease are described. In contrast to 99mTc-CI2 (DMPE)2, 99mTc-TBI could be used successfully for the assessment of ischemic and infarcted myocardial tissue. Yet in general, 201TI scintigraphic findings remained superior. However, from the considerable improvements achieved it is likely that soon a 99mTc-labeled tracer will be available to serve as clinical useful myocardial imaging agent